Versatility of Liposomes for Antisense Oligonucleotide Delivery: A Special Focus on Various Therapeutic Areas - Raghav Gupta; Sagar Salave; Dhwani Rana; Bharathi Karunakaran; Arun Butreddy; Derajram Benival; Nagavendra Kommineni (MDPI AG, 2023)
Nucleic acid therapeutics, specifically antisense oligonucleotides (ASOs), can effectively modulate gene expression and protein function, leading to long-lasting curative effects. The hydrophilic nature and large size of oligonucleotides present translational challenges, which have led to the exploration of various chemical modifications and delivery systems. The present review provides insights into the potential role of liposomes as a drug delivery system for ASOs. The potential benefits of liposomes as an ASO carrier, along with their method of preparation, characterization, routes of administration, and stability aspects, have been thoroughly discussed. A novel perspective in terms of therapeutic applications of liposomal ASO delivery in several diseases such as cancer, respiratory disease, ophthalmic delivery, infectious diseases, gastrointestinal disease, neuronal disorders, hematological malignancies, myotonic dystrophy, and neuronal disorders remains the major highlights of this review.